Using Continuous Turbidity and Seismic Measurements to Unravel Sediment Provenance and Interaction Between Suspended and Bedload Transport in an Alpine Catchment. Issue 4 (12th February 2021) - Misset, C.; Recking, A.; Legout, C.; Bakker, M.; Gimbert, F.; Geay, T.; Zanker, S.
Abstract: Fine sediment transport results from the complexity of the interactions between the different modes of transport and the variety of possible sediment sources, from the river bed stocks remobilization to hillslopes erosion. From a 2‐year period in an Alpine catchment, we show how the combined use of continuous turbidity and seismic measurements can help to address these issues. In the studied catchment, the signals are more strongly correlated during the high flows of the snowmelt period than during the summer period when the river bed is stable and the hillslopes are no longer protected by a snow cover during storms. This sheds light on the seasonal control exerted by the river bed mobility and the snow cover on suspended sediment dynamics in mountainous catchments. It also questions the potential shift of this dynamics from river bed to hillslope dominated in a context of global warming. Plain Language Summary: Suspended sediment transport is a critical process for hydraulic structures and water system management or to understand landscape evolution. Suspension results from complex interactions with the river bed and the variety of possible sediment sources on catchments slopes. These interactions and sources activations are difficult to observe and quantify in the field which partly explain our difficulty to better understand suspended load. From a 2‐year period in an Alpine catchment, we show how the combined use of widely available continuous measurements of suspended load (via water turbidity sensor) and river bed mobility (via seismic sensor) can be used to better understand these processes. During high flows of the snowmelt period, both measurements are correlated. On the contrary, a much variable relation is observed during the summer period when the river bed is stable and the hillslopes are no longer protected by a snow cover during storms. These observations shed light on the seasonal control exerted by the river bed mobility and the snow cover on suspended sediment dynamics in mountainous catchments. It also questions the potential shift of this dynamics from river bed to hillslope dominated in a context of global warming. Key Points: Combining turbidity and seismic measurements in rivers can be used to identify changes in fine sediment sources: river bed versus hillslopes River bed mobility and snow cover exert an important control on suspended load in Alpine catchments Suspended sediment transfer in mountainous environments may shift from river bed to hillslope dominated in a context of global warming